Pengaruh Kombinasi Rebusan Bunga Rosella Dan Madu Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Di Rt 01 Rw 02 Kp. Parung Serab Kelurahan Tirtajaya Kota Depok - Wahid Nugroho Saputra; Bambang Suryadi; Weslei Daeli (Jurnal Intelek Insan Cendikia, 2025)
Hypertension is a condition where blood pressure in the blood vessels is too high, with systolic blood pressure exceeding 140 mmHg or diastolic blood pressure exceeding 90 mmHg. Hypertension is often referred to as a "silent killer" because it can become a deadly disease without early symptoms. Several factors can increase the risk of developing hypertension, including advanced age, genetics, overweight or obesity, lack of physical activity, a high-salt diet, and excessive alcohol consumption. Objective: To determine the effect of a combination of roselle flower decoction and honey on reducing blood pressure in the elderly. Method: This study used a quantitative approach with a quasi- experimental method, employing a one-group pretest and posttest design. This design involves one group that undergoes an initial test (pretest) before receiving treatment and a final test (posttest) after treatment. The sample consisted of 41 elderly individuals with hypertension, selected using a nonprobability sampling method. Results: The study found a p-value of 0.000 (<0.05), indicating that the null hypothesis is rejected and the alternative hypothesis is accepted.Conclusion: There is an effect of the combination of roselle flower decoction and honey on elderly individuals with hypertension in Kp. Parung Serab RT.01 RW.02, Tirtajaya Village.